Entrepreneurship And Marketing Management Outreach For Family Economic Empowerment In Godebag Village - Hermayanto, Ricky; Makarim, Siti Amirah; Dewi, Lati Sari; Fitriani; Nugraha, Yuda; Taufik, Ahmad Royan; Erlangga, Gagas (CV. SINAR HOWUHOWU, 2025)
This community service initiative addresses the entrepreneurial challenges faced by rural families in Godebag Village, Tasikmalaya Regency. Limited business knowledge, poor marketing strategies, and the informal nature of micro-enterprises have hindered economic growth and sustainability. A team from STIE Latifah Mubarokiyah (STIELM) implemented a program using the IPOO (Input–Process–Output–Outcome) framework to enhance local entrepreneurial and marketing capacities. The program involved 35 participants, comprising housewives, youth, and micro-business owners, and focused on business planning, marketing strategies, and participatory learning. As a result, 20 business plans and marketing tools were produced, while 91% of participants expressed high satisfaction. This outreach contributes to building resilient family economies through practical, community-based business education.